Socio-economic development concepts, methodologies, tools, and applications (Information Science Reference, 2019)
"This book provides a critical look at the process of social and economic transformation based on environmental and cultural factors, including income, skills development, employment, and education. Highlighting a range of topics such as economics, social change, and e-governance"--